The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1016/0248-4900(92)90025-v
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the apical cytoskeleton of uterine epithelial cells during early pregnancy in the rat: a study with myosin subfragment 1

Abstract: Actin filaments were identified in the epithelial cells of rat uterus following detergent extraction and decoration of microfilaments (MF) with myosin subfragment 1 (S1). MF connections with cytoplasmic organelles and the apical plasma membrane are also described. Transmission electron microscopy revealed that the regular microvilli of non-pregnant, oestrous animals contain several decorated MF with rootlets descending into a densely filamentous terminal web. Following mating, the actin cytoskeleton was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…Desmosomes (d) are considerably reduced along the lateral plasma membrane at this time and the terminal web is completely lost. membrane of uterine epithelial cells and these changes occupy most of early pregnancy in the rat and mouse with long, regular microvilli being converted into short, irregular structures as early as d 3-2 ~3 d before the blastocyst even enters the uterus [7,[89][90]. As we have also seen, in a wide diversity of species, there are changes in the apical plasma membrane which have features in common with those seen in rats and mice and in many of these other species, closure of the uterine lumen does not occur.…”
Section: "The Plasma Membrane Transforma-tion" Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Desmosomes (d) are considerably reduced along the lateral plasma membrane at this time and the terminal web is completely lost. membrane of uterine epithelial cells and these changes occupy most of early pregnancy in the rat and mouse with long, regular microvilli being converted into short, irregular structures as early as d 3-2 ~3 d before the blastocyst even enters the uterus [7,[89][90]. As we have also seen, in a wide diversity of species, there are changes in the apical plasma membrane which have features in common with those seen in rats and mice and in many of these other species, closure of the uterine lumen does not occur.…”
Section: "The Plasma Membrane Transforma-tion" Conceptmentioning
confidence: 99%
“…They found that in either case, blastocysts were only able to begin implantation when the apical membrane flattening was present. Since this appearance is found in uterine epithelial cells during pseudopregnancy in both mice [8] and rats [9] and can also be induced in virgin ovariectomized rats treated with ovarian hormones in the absence of blastocysts [2,7,11], it must be a maternal response not requiring a blastocyst for its occurrence. This view is further strengthened by the observation that the apical plasma membrane undergoes the same sequence of changes (although perhaps according to a slightly different schedule) whether it is opposed to a blastocyst or to uterine epithelial cells from the other side of the uterus [2, 4, 5, 7-9, 13, 14].…”
Section: The Apical Plasma Membrane In Rodents: Experimental Manipulamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the long and abundant epithelial microvilli retract, creating multiple flat areas in the surface (Schlafke & Enders, 1975;Murphy, 1993). This process could be related to the destabilization of the actin cytoskeletal network observed in these structures (Luxford & Murphy, 1989;Luxford & Murphy, 1992). On the other hand during the receptivity period it has been reported biosynthesis and expression of a different repertoire of surface proteins in the apical (Aplin, 1997;Lessey, 1998;Kirn-Safran & Carson, 1999) and basal-lateral domains (Rogers & Murphy, 1992;Albers et al, 1995;Murphy, 1995;Nikas, 1999).…”
Section: Cellular and Molecular Changes Associated To Endometrial Recmentioning
confidence: 99%
“…Secondary treatment with osmium tetroxide over a period of no more than 2.5 hours is standard for fixation of lipids (Høeg et al, 2004) and this stage may be combined with the primary fixative (Hayat, 1981). There are several embedding media available for TEM ("TAAB": Luxford & Murphy, 1992; "Epon-Araldite": Sloane et al, 1994;"Spurrs": Menzies & Kourteva, 1998;and "LR White": Radford & White, 1998) that differ in their ability to penetrate the specimen and in their hardness; infiltration times of 24 hours are usual for these resins (Paffenhöfer & Loyd, 2000).…”
Section: Introductionmentioning
confidence: 99%